SHP2 단백질 분해활성을 갖는 화합물 및 이들의 의약 용도 - RYU JE HO; PARK JI YOUN; LEE JI HYE; HAN JEONG HWA; AHN JUNG MIN; BAE ONNURI; LEE SOO HYUN; LEE SONG HEE; LIM YE SEUL; KIM JI YOUNG (2024)
본 개시는 SHP2를 분해하는 측면에서 우수한 활성을 갖는 특정 화학구조의 화합물 또는 이의 약학적으로 허용 가능한 염을 제공한다. 본 개시는 또한 이러한 화합물 또는 이의 약학적으로 허용 가능한 염을 포함하는 조성물을 제공한다. 본 개시는 또한 본 개시에 따른 화합물, 이의 염 및 이들을 포함하는 조성물의 SHP2 관련 질환(예를 들어, 암)의 치료 또는 예방용 의약 용도를 제공한다. 본 개시는 또한 본 개시에 따른 화합물, 이의 염 또는 이들을 포함하는 조성물의 유효한 양을 치료가 필요한 개체에게 투여하는 것을 포함하는 SHP2 관련 질환(예를 들어, 암)의 치료 또는 예방 방법을 제공한다. The present disclosure provides a compound having a specific chemical structure or a pharmaceutically acceptable salt thereof having excellent activity in terms of degrading SHP2. The present disclosure also provides a composition comprising such a compound or a pharmaceutically acceptable salt thereof. The present disclosure also provides a medical use of a compound according to the present disclosure, a salt thereof, and a composition comprising the same for the treatment or prophylaxis of SHP2-related diseases (e.g., cancer). The present disclosure also provides a method for treating or preventing a SHP2-related disease (e.g., cancer) comprising administering to a subject in need thereof an effective amount of a compound according to the present disclosure, a salt thereof, or a composition comprising the same.